(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
The discussion article offered here casts doubt on the rightness of the Breakthrough Prize Committee, which 10 years ago awarded its multi-million-dollar bonus to a triple of American astrophysicists A.G.Riess – S.Perlmutter – B.P.Schmidt. Although let’s still clarify: in this case we are not talking about a technical faults in measuring the color spectrum or luminosity of the fuzzy supernovae (which they directly dealt with), but about the subsequent too free interpretation of obtained results, that ultimately led to a general dominant influence of the term "dark energy". However, besides, the author in his article also makes a bold attempt to debunk (or, at least, a little "to ground”) one more eternal mind-disturbing cosmic mystery, connected with the phenomenon of "silentium universi". While, to what extent he succeeded really in that - is up to you, dear readers. And nevertheless the appropriate conclusion obviously suggests here itself: when unraveling the most difficult outlook problems of cosmology, it is better to trust, of course, philosophers rather than naturalists or techies!